Basic Education Services in Cimahi City - Rudiansah, Bambang (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research is motivated by the suboptimal quality of the Delay in the distribution of BOS fund programs for elementary education in Cimahi City is influenced by the existence of inaccurate data so that the distribution of these aid funds is considered suboptimal. This study uses the theory of service quality from Parasuraman (2002) which includes physical evidence, reliability, responsiveness, assurance, empathy. In this study, a qualitative descriptive method approach was used, by describing the distribution of School Operational Assistance funds in Cimahi City. The location of this research is at the Cimahi City Education Office. The results of this study, there were still inaccurate data and invalid education unit account numbers, so the Cimahi City Education Office confirmed and verified the education unit to be able to ensure the accuracy of the data by means of interactive communication between the Cimahi City Education Office and the education unit. In addition, the distribution of School Operational Assistance funds in Cimahi City.